Investigating success factors required in science communication - Phage, I. (South African Journal of Higher Education, 2025)
This study is based on the perception of the importance of owning or having a Science Centre or Museum at the South African University of Technology (UoT). A qualitative study was done with 63 UoT students, and participation was voluntary. The scope of science communication has therefore been limited to people already practicing or learning in the field. The study has thus investigated the key factors to successful science communication in a broader perspective and sphere. The study was also based on the fact that there is no forum of general public science understanding and awareness within and outside UoT communities. UoT will therefore serve as a better platform to communicate science within its community. In turn, the general public and school learners from lower grades can benefit significantly through this endeavour. The study therefore recommends that a Science Centre or Museum, to serve the general public, learners, and students, should be established to serve one of the Metropolitan cities, and its neighbouring regions. The initiative will be in line with the government’s strategic priorities through the DST and foster cooperation and collaboration mainly with the DBE and DHET, with the introduction of skills programmes.